A new species of Aspidomorphus (Serpentes: Elapidae) from Papua New Guinea - Kraus, Fred (Zootaxa, 2025)
Papuan snakes of the genus Aspidomorphus have long been taxonomically problematic, but nomenclature within this group has been stable at three recognized species since 1967. Previous genetic work suggested the presence of a number of cryptic but currently unrecognized candidate species in the genus. In 2004, I obtained a series of Aspidomorphus from Sudest Island, Milne Bay Province, Papua New Guinea that were clearly different from currently recognized species, and I describe that species here as A. dimorphus sp. nov. This species exhibits a striking bimodality in color pattern in adults, here termed the “orange morph” and “dark morph”. This dimorphism is not related to sex, and both forms have earlier been shown to be genetically identical. Description of A. dimorphus sp. nov. begins the process of bringing taxonomic clarity to a genus long held in the grip of nomenclatural stasis. It furthermore highlights again the importance of Sudest Island for biodiversity endemism.